Reproduction of Volcanic Rituals in Appealing for the Right to Live in Disaster-Prone Zones on Mount Merapi - Hudayana, Bambang (Masyarakat, Kebudayaan dan Politik, 2021)
In response to the Mount Merapi eruption in 2010, the government had conducted several disaster risk reduction programs. However, the programs had ironically threatened hamlets as communities regarding their rights to practice their local knowledge and live in their home ground. This study employed a qualitative method involving five hamlets from December 2019 until February 2020. The data were collected by employing participatory observation and depth interviews, involving the ritual organizers, participants, citizens, guests, and other audience. Spirited by ritual theory as political action, this research showed that the hamlets formulated volcanic ritual reproductions into three forms which were the delegitimation of the disaster risk reduction programs, the reinforcement of Kejawen identity, and the showing off the safety and prosperity. Those reproductions were recognized by the emergence of new ritual processions in the forms of parades, pilgrimages, offerings, and enhancements of ritual formalization and celebrations. Those reproductions positively impacted the literacy and recognition from both the government and general society that those hamlets have been living a safe and prosperous life in Merapi, even though they are located in disaster-prone areas.